2019
DOI: 10.1038/s41390-019-0619-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activity of the diaphragm following a loading dose of caffeine citrate in ventilated preterm infants

Abstract: Conflict of interest:Professor Greenough has a non-conditional educational grant from SLE to support her research on optimising neonatal ventilation. Category of study: ClinicalWhat is the key message of your article?• Intravenous administration of caffeine citrate in ventilated, prematurely born neonates transiently increased the diaphragmatic EMG activity and improved respiratory function. What does it add to the existing literature?• This is the first study to assess the impact of caffeine on the diaphragma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Therefore, in our study the immediate evaluation within 5 minutes was chosen for re-evaluation of diaphragm activity to identify the change after caffeine loading dose. On the other hand, Williams et al 13 evaluated 32 infants under 34 gestational week born by using dEMG before and after caffeine loading dose and identi ed a signi cant increase in dEMG amplitude at 25 minutes that peaked at 30 minutes 13 . Therefore, the evaluation at 5 minutes rather than at 25 minutes may be the reason of no change in the right diaphragm thicknesses and velocities observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in our study the immediate evaluation within 5 minutes was chosen for re-evaluation of diaphragm activity to identify the change after caffeine loading dose. On the other hand, Williams et al 13 evaluated 32 infants under 34 gestational week born by using dEMG before and after caffeine loading dose and identi ed a signi cant increase in dEMG amplitude at 25 minutes that peaked at 30 minutes 13 . Therefore, the evaluation at 5 minutes rather than at 25 minutes may be the reason of no change in the right diaphragm thicknesses and velocities observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other methylxanthines, caffeine was shown to have a greater effect on diaphragm than theophylline in both experimental and clinical studies 10,11 . The treatment also increased diaphragmatic activity, tidal volume, lung function and muscle strength in preterm babies 2,12,13 . There were two studies included preterm infants and showed transient increase in electrical activity of the diaphragm after caffeine assignment 12,13 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…An alternative explanation for our negative results is that transcutaneous measurements were too insensitive to detect differences. We, however, think this is unlikely as we have demonstrated changes in the transcutaneous EMG signal following the administration of a loading dose of caffeine [22]. We calculated the NVE using expiratory tidal volumes, as these are less prone to errors due to leak around the endotracheal tube and we used Coles tubes around which there is minimal or no leak [23].…”
Section: Discussionmentioning
confidence: 99%